Cabinet Formation Elections: Among Opposition, Coalition, or Collegiality of The Party’s Chairperson - Sulardi Sulardi; Wafda Vivid Izziyana (Alliance of Health Activists (AloHA), 2020)
Constitutional change is always tinged with a tense and lasting political constellation in both national and international contexts. the existence of transactional politics to gain seats constantly influences political dynamics in the election period. The method used in this research is the doctrinal method. Indonesia applies a presidential government system but does not fully follow the existing doctrine. several coalitions in the government coalition were made. As a result when the President and Vice President are nominated. political parties that support the nomination feel they have the right to join the government, as in the parliamentary system of government. The cabinet filling model is also influenced by supporting parties. It shows that political parties can collaborate to form a joint government, however, the President has the prerogative in determining who will be his minister. It should be carefully noted down that our country is a country adopting a presidential government system. As a result, the formation and the ministers elections of the government is not at the hand of the chairperson of the political parties coalition, but fully at the hand of the president as the President’s prerogative rights. This cannot be proceeded. Chairperson of the Political parties in a coalition may expect to get some seats of powers (minister) from the President Keywords: cabinet; election; political; party; chairperson